Analysis of the Water Quality of Padolo River, Bima District - Tina Melinda; Muhamad Majdi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
A river is a body of water characterized by a current flowing from upstream to downstream to the estuary. River water quality is influenced by both natural and human factors, as rivers serve as a venue for various activities. The purpose of this research is to assess the water quality of the Padolo River, as measured by chemical parameters. This type of research is descriptive quantitative. the chemical parameters tested in this study were pH, BOD, COD and DO. pH testing on water samples was conducted using the pH meter method, while BOD, COD, and DO testing were performed using the Winkler method. The research results indicate that the pH levels in the upstream, middle, and downstream sections are the same, specifically 6.9. The BOD value in the upstream section is 10.8 mg / L, the middle section 9.5 mg / L and in the downstream section 18 mg / L, while the COD value in the upstream section is 28 mg / L, the middle section 24 mg / L and in the downstream section 32 mg / L and the DO value in the upstream section is 5.8 mg / L, the middle section 6.8 mg / L and in the downstream section 7.9 mg / L.. Based on the measurement results and government regulation no. 22 of 2021 concerning river water parameter standards, it is stated that the BOD and DO values ​​do not meet the specified quality standards. It is hoped that the local government will conduct routine water quality measurements in the Padolo River, considering that the water is used by residents for bathing, washing, and toilet purposes.